2021
DOI: 10.1136/neurintsurg-2020-017242
|View full text |Cite
|
Sign up to set email alerts
|

Suction force rather than aspiration flow correlates with recanalization in hard clots: an in vitro study model

Abstract: BackgroundANA Advanced Neurovascular Access provides a novel funnel component designed to reduce clot fragmentation and facilitate retrieval in combination with stent-retrievers (SRs) in stroke patients by restricting flow and limiting clot shaving. In previous publications ANA presented excellent in vitro/in vivo efficacy data, especially with fibrin-rich hard clots. We aimed to determine the main physical property responsible for these results, namely suction force versus aspiration flow.MethodsWe evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The expanded funnel confers a substantial increase in suction force compared with other catheters, specifically in combination with a SR that contributes to the efficacy to retrieve the clot. 12 All participating interventionalists were trained on the use of the ANA device before start of enrollment. The training was performed on a simulation cerebrovascular model where procedural steps including navigation and removal of an artificial clot were practiced.…”
Section: Methodsmentioning
confidence: 99%
“…The expanded funnel confers a substantial increase in suction force compared with other catheters, specifically in combination with a SR that contributes to the efficacy to retrieve the clot. 12 All participating interventionalists were trained on the use of the ANA device before start of enrollment. The training was performed on a simulation cerebrovascular model where procedural steps including navigation and removal of an artificial clot were practiced.…”
Section: Methodsmentioning
confidence: 99%
“…The MIVI Q™ aspiration catheter is designed to maximize lumen size, increasing flow rates and tip suction force [ 11 ]. Both properties combined have been shown to be necessary to effectively extract the clot, but in vitro experiments indicated that suction force is more relevant than aspiration flow in terms of efficacy, particularly in hard clots [ 27 ]. The MIVI Q TM exhibits these two physical properties, and especially the aspiration flow rate benefits from a dynamic effect as in vitro testing has demonstrated that it increases as the Q TM is retracted inside the guiding catheter [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NIHSS National Institute of Health Stroke Scale score, IQR interquartile range, mRS modified Rankin Scale score, sICH symptomatic intracranial hemorrhage, ICH intracranial hemorrhage a Early neurological improvement was defined as a reduction of ≥ 5 points on the NIHSS or an NIHSS score < 4 at 24-hours b Microwire perforation with contrast extravasation on angiography MIVI Q™ aspiration catheter is designed to maximize lumen size, increasing flow rates and tip suction force [11]. Both properties combined have been shown to be necessary to effectively extract the clot, but in vitro experiments indicated that suction force is more relevant than aspiration flow in terms of efficacy, particularly in hard clots [27]. The MIVI Q TM exhibits these two physical properties, and especially the aspiration flow rate benefits from a dynamic effect as in vitro testing has demonstrated that it increases as the Q TM is retracted inside the guiding catheter [11].…”
mentioning
confidence: 99%
“…In line with the theoretical equations, technical in vitro evaluations by several authors suggest that the aspiration performance (both in terms of force and flow rate) of distal access catheters is highly dependent on the labeled inner diameter specified by device manufacturers. 8,[14][15][16][17][18][19] However, this rationale is only applicable when the thrombus is softer than the catheter tip and only the clot experiences strain (e.g., erythrocyte-rich thrombus). 20 In reality, the distal edge above the radiopaque marker band of the catheters is the softest part of the device, commonly constituted by the liner and/or the polymeric jacket layer.…”
Section: Aspirationmentioning
confidence: 99%